Pengaruh Kualitas Produk dan Harga terhadap Kepuasan Pengguna Smartphone Oppo Reno di Kecamatan Maiwa Kabupaten Enrekang - Marwah Marwah; Burhanuddin Burhanuddin; Muhammad Ilham Wardhana Haeruddin; Chalid Imran Musa; Muhammad Ichwan Musa (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This exploration plans to decide and break down the impact of item quality on the fulfillment of Oppo Reno Cell phone clients in Maiwa Area, Enrekang Regime. To decide and break down the impact of cost on client fulfillment of Oppo Reno Cell phones in Maiwa Area, Enrekang Regime. This sort of exploration is enlightening quantitative, by conveying surveys with an example size of 110 respondents or Oppo Reno cell phone clients in Maiwa Locale, Enrekang Regime. Then, at that point, the information investigation utilized is numerous direct relapse examination. The consequences of this study are that there is a positive and critical impact between item quality on the fulfillment of Oppo Reno cell phone clients in Maiwa Locale, Enrekang Regime. There is a positive and huge impact among cost and client fulfillment of Oppo Reno cell phones in Maiwa Locale, Enrekang Regime. In light of the consequences of exploration utilizing the F test, it shows that item quality and cost all the while altogether affect the fulfillment of Oppo Reno cell phone clients in Maiwa Area, Enrekang Regime.